(3bjGS eDTQGJ XGgQI GdabQ aj GdhWf GdYQHj (B/s - (3GdYPGQj, OGhO eMeO YOfGfs; (3GdOYej, gOi RhjQ eNda s ((3YeGf(B: s (3OGQ LQjQ(B, s, 2010)
(3fXQI aj eaGgje GdabQ hfXQjGJg, XGgQI GdabQ aj GdhWf GdYQHj, GdJMdjd Gdcej GdGbJUGOjs
(3GdeQGLY HGdYQHjI hGdCLfHjI U(B.183 (3dedGMb U(B.199s
Keywords: (3GdabQs; (3GdabQ (B-(3GdhWf GdYQHjs